Ni and stainless steel fiber / porous aluminum composite material and preparation method thereof
By introducing Ni@ stainless steel fibers into the porous aluminum sound-absorbing material and performing in-situ diffusion treatment, an interface diffusion layer of Ni and Al is formed, which solves the problem of low mechanical properties of porous aluminum materials and achieves the effect of high sound absorption and high strength of the material.
Patent Information
- Application Number
- CN202510082506.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Due to its unique porous structure, porous aluminum sound absorbing materials have good sound absorption properties, but their mechanical properties are relatively low, making it difficult to have both high sound absorption and high intensity.
Ni@ stainless steel fibers are used as the reinforced phase, and prepared by seepage method and in-situ diffusion treatment is carried out to form an interface diffusion layer of Ni and Al to enhance the interface bonding strength of the material.
It improves the compression yield strength of Ni@ stainless steel fiber/porous aluminum composite material, and has high sound absorption and high intensity performance, meeting the application needs of technical fields such as sound absorption and noise reduction.
Smart Images

Figure CN119876797A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a Ni@stainless steel fiber / porous aluminum composite material and a preparation method thereof, and belongs to the field of porous sound-absorbing composite materials. Background Art
[0002] Noise pollution is listed as one of the four major pollution sources today, and its control is the most difficult. In order to reduce the impact of noise pollution on human physical and mental health, sound absorption is one of the effective ways to mitigate noise pollution. Sound-absorbing materials can be divided into two categories according to different mechanisms: porous sound-absorbing materials and resonance sound-absorbing materials. The sound absorption mechanism of resonance materials is to convert sound energy into mechanical energy of vibration through material vibration, and then into heat energy. Resonance materials have a high sound absorption coefficient at medium and low frequencies, but their own complex structure and high cost are not conducive to large-scale production. Porous sound-absorbing materials can effectively absorb and attenuate sound wave energy through their unique physical structure and material properties. When sound waves are incident on porous sound-absorbing materials, the sound energy is mainly absorbed by the porous sound-absorbing materials through the heat dissipation generated by the friction between air molecules and pore walls, and the heat dissipation and viscous dissipation of airflow between the pores inside the material.
[0003] The raw materials of porous sound absorption include metal, ceramic and synthetic resin. Common porous metal sound absorption materials include porous aluminum, porous nickel, porous magnesium, porous iron and porous titanium. Among them, porous aluminum is widely used in the fields of construction, aerospace, automobile, public facilities, etc. due to its advantages such as high porosity, high specific strength, strong heat transfer and heat dissipation capacity, light weight and easy handling. Such as: automobile interior, engine compartment and body panels, which effectively reduce the noise generated by the operation of the vehicle; jet aircraft engine hood, sound insulation cover of mechanical equipment and other parts. However, due to its unique porous structure, although porous aluminum has good sound absorption performance, its mechanical properties are relatively low. Therefore, how to make it have high strength properties while ensuring its high sound absorption performance is an important problem that needs to be solved.
[0004] In order to improve the mechanical properties of porous metal sound-absorbing materials, the present invention uses Ni@stainless steel fiber as a reinforcing phase, adopts an infiltration method to prepare an infiltration precursor sample, and then performs in-situ diffusion treatment to allow nickel and aluminum atoms in the AlSi12 alloy matrix to undergo atomic diffusion migration at high temperature to form an in-situ diffusion interface, thereby achieving the purpose of fully utilizing the high-strength characteristics of the reinforcement to enhance the interfacial bonding strength of the porous sound-absorbing material, and obtaining a Ni@stainless steel fiber / porous aluminum composite material with both high strength and high sound absorption performance. Summary of the invention
[0005] In order to solve the problem described in the technical background, the present invention provides an in-situ diffusion enhanced Ni@stainless steel fiber / porous aluminum composite material, wherein the composite material is based on AlSi12 alloy, Ni@stainless steel fiber is a reinforcing phase, and a Ni and Al interface diffusion layer is formed by a percolation and in-situ diffusion method to obtain an in-situ diffusion composite enhanced Ni@stainless steel fiber / porous aluminum composite material, wherein the thickness of the Ni and Al interface diffusion layer is 1.25μm to 3.01μm, the porosity is 80% to 84%, and the volume fraction of the stainless steel fiber in the Ni@stainless steel fiber / porous aluminum composite material is 8vol.% to 10vol.%.
[0006] The in-situ diffusion composite reinforced Ni@stainless steel fiber / porous aluminum composite material has a compressive yield strength of 1.69MPa to 3.66MPa, which is 4.78% to 6.81% higher than that of the stainless steel fiber / porous aluminum composite material with the same porosity and pore size.
[0007] The thickness of the Ni and Al interface diffusion layer is 1.25 μm to 3.01 μm, the volume fraction of the stainless steel fiber in the Ni@stainless steel fiber / porous aluminum composite material is 8 vol.% to 10 vol.%, and the porosity is 80% to 84%.
[0008] The object of the present invention is to provide a method for preparing the Ni@stainless steel fiber / porous aluminum composite material, wherein a composite interface is formed by atomic diffusion; the interface has good bonding performance and can effectively improve the overall strength of the material; the stainless steel fiber is nickel-plated, the nickel-plated stainless steel fiber is mixed with salt, pressed into a preform, the aluminum melt infiltrates the preform to obtain the Ni@stainless steel fiber / aluminum composite material, washed with water to remove the salt, and in-situ diffused to obtain the Ni@stainless steel fiber / porous aluminum composite material; by controlling the diffusion temperature and time, only atomic diffusion occurs at the interface between the stainless steel fiber and the porous aluminum matrix without chemical reaction, avoiding the formation of an intermediate phase, and forming a Ni, Al interface diffusion layer, which specifically comprises the following steps:
[0009] (1) Nickel is plated on the surface of stainless steel fiber to obtain Ni@stainless steel fiber, the Ni@stainless steel fiber and NaCl particles are mixed to obtain a mixture, and then pressed into a preform.
[0010] (2) After the AlSi12 alloy is heated and melted, the aluminum alloy melt is pressed into the pores of the preform by the infiltration method to prepare a Ni@stainless steel fiber / aluminum composite material containing NaCl.
[0011] (3) Ni@stainless steel fiber / aluminum composite material containing NaCl is dissolved in water to obtain Ni@stainless steel fiber / porous aluminum composite material.
[0012] (4) The Ni@stainless steel fiber / porous aluminum composite material is heated, diffused in situ, and air-cooled to obtain an in-situ diffusion-reinforced Ni@stainless steel fiber / porous aluminum composite material.
[0013] Preferably, in step (1) of the present invention, the NaCl particles are 0.5 mm to 0.8 mm, the stainless steel fibers have a diameter of 20 μm to 60 μm, and a length of 1 mm to 3 mm.
[0014] Preferably, in the mixture of step (1) of the present invention, the mass percentage of Ni@stainless steel fibers is 2% to 3%, and the mass percentage of NaCl particles is 97% to 98%.
[0015] Preferably, the pressing pressure for preparing the preform in step (1) of the present invention is 24 kN to 26 kN.
[0016] Preferably, the pressure used in the seepage method in step (2) of the present invention is 0.4 MPa to 0.6 MPa.
[0017] Preferably, in step (4) of the present invention, the in-situ diffusion temperature is 350° C. to 450° C., and the insulation time is 30 to 75 minutes.
[0018] Preferably, the specific process of nickel plating the surface of the stainless steel fiber of the present invention is:
[0019] (1) The stainless steel fiber is degreased and debonded and then washed with water; etched with 5% to 8% NaOH for 30 to 45 minutes and washed with water; sensitized with SnCl2 at a concentration of 8 g / L to 12 g / L for 3 minutes to 5 minutes and washed with water; activated with a silver ammonia solution at a concentration of 10 g / L to 15 g / L for 5 minutes to 10 minutes and washed with water;
[0020] (2) The stainless steel fiber is electroplated with a nickel plating solution at 70-85° C. and a pH value of 4.5-5.5 for 40 min-60 min; the nickel plating solution comprises: 20 g / L-30 g / L nickel sulfate, 20 g / L-25 g / L potassium borohydride, 20 g / L-30 g / L boric acid, 1 mg / L-2 mg / L thiourea and additives.
[0021] (3) Wash with water and dry.
[0022] The AlSi12 alloy melt is pressed into the pores of the infiltration preform, so that the Ni@stainless steel fiber and the AlSi12 alloy are composited to form an in-situ diffusion-enhanced Ni@stainless steel fiber / porous aluminum composite material. On the one hand, the Ni@stainless steel fiber exists in the AlSi12 porous material in the form of pore wall fibers, interpore fibers and perforations. When subjected to stress, the stainless steel fibers in the matrix will deflect and displace, thereby offsetting part of the compression energy, transmitting and dispersing stress, and reducing local stress concentration. At the same time, the stainless steel fiber can also pin cracks, inhibit crack propagation, hinder compressive strain and change the compression collapse path, thereby improving the ability of the porous material to resist external force deformation, and then improving the compressive yield strength of the in-situ diffusion-enhanced Ni@stainless steel fiber / porous aluminum composite material. On the other hand, nickel atoms and aluminum atoms in AlSi12 undergo atomic diffusion at high temperature to form a stable interface. This interface tightly connects the stainless steel fiber to the matrix, effectively transmits the stress between the fiber and the matrix, reduces the stress concentration at the interface, and enhances the overall strength, stiffness and impact resistance of the material. At the same time, this also improves the durability and stability of the composite material. Therefore, the interface formed by the atomic diffusion mechanism plays a key role in the interface reinforcement in the in-situ diffusion-enhanced Ni@stainless steel fiber / porous aluminum composite.
[0023] Principle of the Invention
[0024] (1) Principle of thickness control of in-situ composite interface diffusion layer:
[0025] In-situ diffusion refers to the phenomenon that atoms spontaneously migrate from high-concentration areas to low-concentration areas in solid materials due to the effects of temperature, concentration gradient or other external force fields, which can be explained by Fick's law. Therefore, under high temperature conditions, the aluminum atoms in the matrix AlSi12 and the nickel atoms on the nickel-plated stainless steel fibers will undergo in-situ diffusion and migration, forming a stable and uniform ideal interface between the stainless steel fibers and the aluminum alloy matrix; therefore, the in-situ diffusion composite method is adopted to control the thickness of the in-situ composite interface diffusion layer to prevent the formation of brittle phases, and obtain an ideal interface where only atomic diffusion occurs as much as possible.
[0026] For the planar diffusion case, the diffusion thickness model formula is:
[0027]
[0028] Where D0 is the diffusion coefficient (unit: m 2 / s), Q is the activation energy (unit: KJ / mol), R is the gas coefficient (J / (mol·K)), and T is the absolute temperature (unit: K).
[0029] Due to the small atomic radius of aluminum, the low melting point and the vacancy diffusion mechanism followed in substitutional solid solution, the diffusion rate of aluminum in nickel is much greater than the diffusion rate of nickel in aluminum. Therefore, it can be approximately regarded as aluminum diffusion in nickel, taking D0≈1.2×8 -4 m 2 / s, Q≈131KJ / mol, R≈8.314J / (mol·K), when the time is 30min~75min, substituting the temperature of 350℃ and 450℃ into the above formula, the diffusion layer thickness under different conditions can be obtained.
[0030] (2) In-situ diffusion composite enhancement principle:
[0031] In the process of in-situ diffusion composite, the ideal interface between Ni@stainless steel fiber and aluminum matrix should only undergo in-situ diffusion to form a uniform diffusion layer with a clean interface and no other brittle phases. The thickness, uniformity and purity of the atomic diffusion layer determine the strength of the metallurgical bonding interface. When the diffusion temperature and time exceed 640℃ and 75min, brittle intermetallic compounds will form between nickel and AlSi12 alloy matrix, which will lead to the formation and expansion of microcracks inside the material, thereby weakening the interface bonding strength. Therefore, in-situ diffusion composite is adopted to control the time and temperature of in-situ diffusion to prevent the formation of brittle phases.
[0032] Combining the Gibson-Ashby model with the experimental data, the relationship between the porosity and compressive yield strength of the Ni@stainless steel fiber / porous aluminum composite material can be obtained:
[0033] σ c =1.087(1-ρ) -0.899
[0034] Among them, σ c : compressive yield strength of Ni@stainless steel fiber / porous aluminum composite material (MPa), ρ: porosity of Ni@stainless steel fiber / porous aluminum composite material.
[0035] The relationship between the compressive yield strength and porosity of stainless steel fiber / porous aluminum composite materials with the same pore size (0.5 mm) is:
[0036]
[0037] in, Compressive yield strength of stainless steel fiber / porous aluminum composites (MPa), ρ0: porosity of stainless steel fiber / porous aluminum composites.
[0038] Beneficial effects of the present invention
[0039] The in-situ diffusion composite reinforced Ni@stainless steel fiber / porous aluminum composite material obtained by the infiltration method has a compressive yield strength of 1.69MPa to 3.66MPa, which is 4.78% to 6.81% higher than the compressive yield strength of the stainless steel fiber / porous aluminum composite material with the same porosity and pore size. A composite interface is generated by atomic diffusion between the nickel atoms on the surface of the stainless steel fiber and the aluminum atoms in the porous aluminum matrix, and the interface bonding force is improved. It has both high strength and high sound absorption characteristics, and can meet the application requirements in the technical fields of sound absorption and noise reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Process flow chart of Ni@stainless steel fiber / porous aluminum composite material. DETAILED DESCRIPTION
[0041] Example 1
[0042] In this embodiment, an in-situ diffusion composite reinforced Ni@stainless steel fiber / porous aluminum composite material is prepared by the following steps.
[0043] (1) Degreasing and degumming of stainless steel fiber with a diameter of 20 μm and a length of 1 mm.
[0044] (2) The stainless steel fiber is pretreated by washing with deionized water, drying in a drying oven, etching with 5% NaOH solution, washing with deionized water, and drying.
[0045] (3) Electroless nickel plating was performed at 70°C and pH 4.5 for 40 min using a nickel plating solution containing 30 g / L nickel sulfate, 25 g / L potassium borohydride, 30 g / L boric acid, 2 mg / L thiourea and other additives, followed by washing with water and drying to obtain Ni@stainless steel fibers.
[0046] (4) NaCl particles with a particle size of 0.5 mm and Ni@stainless steel fibers with a volume fraction of 8 vol.% to 10 vol.% are mixed, and pressed and maintained at a pressure of 26 MPa for 5 minutes to obtain a mixed preform of Ni@stainless steel fibers and salt particles.
[0047] (5) The AlSi12 alloy is heated to 650°C to melt, and the AlSi12 alloy melt is pressed into the pores of the Ni@stainless steel fiber and salt particle mixed preform at a pressure of 0.4 MPa to obtain a salt-containing Ni@stainless steel fiber / aluminum composite material.
[0048] (6) The salt-containing Ni@stainless steel fiber / aluminum composite material is desalted by water to obtain a Ni@stainless steel fiber / porous aluminum composite material with a porosity of 84%.
[0049] (7) The Ni@stainless steel fiber / porous aluminum composite material was subjected to in-situ diffusion treatment at a temperature of 350°C and insulation for 30 min, so that the nickel on the surface of the Ni@stainless steel fiber and the aluminum matrix underwent atomic diffusion to form a composite interface. After air cooling, an in-situ diffusion composite-reinforced Ni@stainless steel fiber / porous aluminum composite material with an interface diffusion layer thickness of 1.25 μm and a compressive yield strength of 1.69 MPa was obtained, which is 4.78% higher than the compressive yield strength of the stainless steel fiber / porous aluminum composite material with the same porosity and pore size.
[0050] Example 2
[0051] In this embodiment, an in-situ diffusion composite reinforced Ni@stainless steel fiber / porous aluminum composite material is prepared by the following steps.
[0052] (1) Degreasing and degumming of stainless steel fiber with a diameter of 20 μm and a length of 1 mm.
[0053] (2) The stainless steel fiber is pretreated by washing with deionized water, drying in a drying oven, etching with 5% NaOH solution, washing with deionized water, and drying.
[0054] (3) Electroless nickel plating was performed at 75°C and pH 4.5 for 45 min using a nickel plating solution containing 30 g / L nickel sulfate, 25 g / L potassium borohydride, 30 g / L boric acid, 2 mg / L thiourea and other additives, followed by washing with water and drying to obtain Ni@stainless steel fibers.
[0055] (4) NaCl particles with a particle size of 0.5 mm and Ni@stainless steel fibers with a volume fraction of 8 vol.% to 10 vol.% are mixed, and the pressure is maintained at 25.5 MPa for 5 minutes to obtain a mixed preform of Ni@stainless steel fibers and salt particles.
[0056] (5) The AlSi12 alloy is heated to 650°C to melt, and the AlSi12 alloy melt is pressed into the pores of the Ni@stainless steel fiber and salt particle mixed preform at a pressure of 0.4 MPa to obtain a salt-containing Ni@stainless steel fiber / aluminum composite material.
[0057] (6) The salt-containing Ni@stainless steel fiber / aluminum composite material is desalted in water to obtain a Ni@stainless steel fiber / porous aluminum composite material with a porosity of 83%.
[0058] (7) The Ni@stainless steel fiber / porous aluminum composite material was subjected to in-situ diffusion treatment at a temperature of 350°C and a heat preservation time of 45 min, so that the nickel on the surface of the Ni@stainless steel fiber and the aluminum matrix underwent atomic diffusion to form a composite interface. After air cooling, an in-situ diffusion composite-reinforced Ni@stainless steel fiber / porous aluminum composite material with an interface diffusion layer thickness of 1.51 μm and a compressive yield strength of 2.13 MPa was obtained, which is 4.96% higher than the compressive yield strength of the stainless steel fiber / porous aluminum composite material with the same porosity and pore size.
[0059] Example 3
[0060] In this embodiment, an in-situ diffusion composite reinforced Ni@stainless steel fiber / porous aluminum composite material is prepared by the following steps.
[0061] (1) Degreasing and degumming of stainless steel fiber with a diameter of 20 μm and a length of 1 mm.
[0062] (2) The stainless steel fiber is pretreated by washing with deionized water, drying in a drying oven, etching with 5% NaOH solution, washing with deionized water, and drying.
[0063] (3) Electroless nickel plating was performed at 80°C and pH 4.5 for 50 min using a nickel plating solution containing 30 g / L nickel sulfate, 25 g / L potassium borohydride, 30 g / L boric acid, 2 mg / L thiourea and other additives, followed by washing with water and drying to obtain Ni@stainless steel fibers.
[0064] (4) NaCl particles with a particle size of 0.5 mm and Ni@stainless steel fibers with a volume fraction of 8 vol.% to 10 vol.% are mixed, and pressed and maintained at a pressure of 25 MPa for 5 minutes to obtain a mixed preform of Ni@stainless steel fibers and salt particles.
[0065] (5) The AlSi12 alloy is heated to 650°C to melt, and the AlSi12 alloy melt is pressed into the pores of the Ni@stainless steel fiber and salt particle mixed preform at a pressure of 0.4 MPa to obtain a salt-containing Ni@stainless steel fiber / aluminum composite material.
[0066] (6) The salt-containing Ni@stainless steel fiber / aluminum composite material is desalted in water to obtain a Ni@stainless steel fiber / porous aluminum composite material with a porosity of 82%.
[0067] (7) The Ni@stainless steel fiber / porous aluminum composite material was subjected to in-situ diffusion treatment at a temperature of 450°C and insulation for 60 min, so that the nickel on the surface of the Ni@stainless steel fiber and the aluminum matrix underwent atomic diffusion to form a composite interface. After air cooling, an in-situ diffusion composite-reinforced Ni@stainless steel fiber / porous aluminum composite material with an interface diffusion layer thickness of 2.52 μm and a compressive yield strength of 2.38 MPa was obtained, which is 6.63% higher than the compressive yield strength of the stainless steel fiber / porous aluminum composite material with the same porosity and pore size.
[0068] Example 4
[0069] In this embodiment, an in-situ diffusion composite reinforced Ni@stainless steel fiber / porous aluminum composite material is prepared by the following steps.
[0070] (1) Degreasing and degumming of stainless steel fiber with a diameter of 20 μm and a length of 1 mm.
[0071] (2) The stainless steel fiber is pretreated by washing with deionized water, drying in a drying oven, etching with 5% NaOH solution, washing with deionized water, and drying.
[0072] (3) Electroless nickel plating was performed at 85°C and pH 4.5 for 60 min using a nickel plating solution containing 30 g / L nickel sulfate, 25 g / L potassium borohydride, 30 g / L boric acid, 2 mg / L thiourea and other additives, followed by washing with water and drying to obtain Ni@stainless steel fibers.
[0073] (4) NaCl particles with a particle size of 0.5 mm and Ni@stainless steel fibers with a volume fraction of 8 vol.% to 10 vol.% are mixed, and pressed and maintained at a pressure of 24 MPa for 5 minutes to obtain a mixed preform of Ni@stainless steel fibers and salt particles.
[0074] (5) The AlSi12 alloy is heated to 650°C to melt, and the AlSi12 alloy melt is pressed into the pores of the Ni@stainless steel fiber and salt particle mixed preform at a pressure of 0.4 MPa to obtain a salt-containing Ni@stainless steel fiber / aluminum composite material.
[0075] (6) The salt-containing Ni@stainless steel fiber / aluminum composite material is desalted by water to obtain a Ni@stainless steel fiber / porous aluminum composite material with a porosity of 80%.
[0076] (7) The Ni@stainless steel fiber / porous aluminum composite material was subjected to in-situ diffusion treatment at a temperature of 450°C and a heat preservation time of 75 min, so that the nickel on the surface of the Ni@stainless steel fiber and the aluminum matrix underwent atomic diffusion to form a good bonding interface. After air cooling, an in-situ diffusion-reinforced Ni@stainless steel fiber / porous aluminum composite material with an interface diffusion layer thickness of 3.01 μm and a compressive yield strength of 3.66 MPa was obtained, which was 6.81% higher than the compressive yield strength of the stainless steel fiber / porous aluminum composite material with the same porosity and pore size.
Claims
1. A Ni@stainless steel fiber / porous aluminum composite material, characterized in that: The composite material uses AlSi12 alloy as a matrix and Ni@stainless steel fiber as a reinforcement phase, and adopts a Ni and Al interface diffusion layer formed by a percolation and in-situ diffusion method to obtain an in-situ diffusion composite reinforced Ni@stainless steel fiber / porous aluminum composite material, wherein the thickness of the Ni and Al interface diffusion layer is 1.25 μm to 3.01 μm, the porosity is 80% to 84%, and the volume fraction of the stainless steel fiber in the Ni@stainless steel fiber / porous aluminum composite material is 8 vol.% to 10 vol.%.
2. The method for preparing the Ni@stainless steel fiber / porous aluminum composite material according to claim 1, characterized in that: The stainless steel fiber is nickel-plated, the nickel-plated stainless steel fiber is mixed with salt, pressed into a preform, and the aluminum melt is infiltrated into the preform to obtain a Ni@stainless steel fiber / aluminum composite material, and the salt is removed by washing with water, and the Ni@stainless steel fiber / porous aluminum composite material is obtained by in-situ diffusion; by controlling the diffusion temperature and time, only atomic diffusion occurs at the interface between the stainless steel fiber and the porous aluminum matrix without chemical reaction, and the formation of an intermediate phase is avoided, and a Ni and Al interface diffusion layer is formed, thereby obtaining an in-situ diffusion-composite-reinforced Ni@stainless steel fiber / porous aluminum composite material.
3. The method for preparing the Ni@stainless steel fiber / porous aluminum composite material according to claim 2, characterized in that: The specific steps include: (1) nickel is plated on the surface of stainless steel fiber to obtain Ni@stainless steel fiber, the Ni@stainless steel fiber and NaCl particles are mixed to obtain a mixture, and then pressed into a preform; (2) After heating and melting the AlSi12 alloy, the aluminum alloy melt is pressed into the pores of the preform by an infiltration method to prepare a Ni@stainless steel fiber / aluminum composite material containing NaCl; (3) using water to dissolve NaCl from the Ni@stainless steel fiber / aluminum composite material to obtain a Ni@stainless steel fiber / porous aluminum composite material; (4) The Ni@stainless steel fiber / porous aluminum composite material is heated, diffused in situ, and air-cooled to obtain an in-situ diffusion-reinforced Ni@stainless steel fiber / porous aluminum composite material.
4. The method for preparing the Ni@stainless steel fiber / porous aluminum composite material according to claim 3, characterized in that: In step (1), the NaCl particles are 0.5 mm to 0.8 mm, the stainless steel fibers have a diameter of 20 μm to 60 μm, and a length of 1 mm to 3 mm.
5. The method for preparing the Ni@stainless steel fiber / porous aluminum composite material according to claim 3, characterized in that: The mass percentage of Ni@stainless steel fiber in the mixture of step (1) is 2% to 3%, and the mass percentage of NaCl particles is 97% to 98%.
6. The method for preparing the Ni@stainless steel fiber / porous aluminum composite material according to claim 3, characterized in that: The pressing pressure for preparing the preform in step (1) is 24 kN to 26 kN.
7. The method for preparing the Ni@stainless steel fiber / porous aluminum composite material according to claim 3, characterized in that: The pressure used in the seepage method in step (2) is 0.4 MPa to 0.6 MPa.
8. The method for preparing the Ni@stainless steel fiber / porous aluminum composite material according to claim 3, characterized in that: In step (4), the in-situ diffusion temperature is 350° C. to 450° C., and the insulation time is 30 to 75 minutes.
9. The method for preparing the Ni@stainless steel fiber / porous aluminum composite material according to claim 3, characterized in that: The specific process of nickel plating on the surface of stainless steel fiber is: (1) The stainless steel fiber is degreased and debonded and then washed with water; etched with 5% to 8% NaOH for 30 to 45 minutes and washed with water; sensitized with SnCl2 at a concentration of 8 g / L to 12 g / L for 3 minutes to 5 minutes and washed with water; activated with a silver ammonia solution at a concentration of 10 g / L to 15 g / L for 5 minutes to 10 minutes and washed with water; (2) chemically nickel-plating the stainless steel fiber with a nickel plating solution at 70 to 85° C. and a pH value of 4.5 to 5.5 for 40 to 60 minutes; the nickel plating solution comprises: 20 g / L to 30 g / L nickel sulfate, 20 g / L to 25 g / L potassium borohydride, 20 g / L to 30 g / L boric acid, 1 mg / L to 2 mg / L thiourea and additives; (3) Wash with water and dry.
Citation Information
Patent Citations
Preparation method of periodic pore structure aluminum alloy / stainless steel fiber composite foam
CN108624828A
Sliding member
JP1988042338A
Reinforcing fiber for production of fiber-reinforced composite metallic material
JP1989111830A
Fiber reinforced composite metallic article and their production
JP1995276034A
Metal matrix composite materials containing carbon nanotube-infused fiber materials and methods for production thereof
US20120164429A1
Cited By
Processing technology of aluminum-based multiphase composite toughness reinforced guide rail for new energy automobile sunroof
CN121852828A